Pathogen-specific DNA sensing with engineered zinc finger proteins immobilized on polymer chip - Ha, Dat Thinh (Analyst, 2018)
A specific double-stranded DNA sensing system is of great interest for diagnostic and other biomedical applications. Zinc finger domains, which recognize double-stranded DNA, can be engineered to form custom DNA-binding proteins for recognition of specific DNA sequences. As a proof of concept, a sequence-enabled reassembly of TEM-1 β-lactamase system (SEER-LAC) was previously demonstrated to develop zinc finger protein (ZFP) arrays for the detection of a double-stranded bacterial DNA sequence. Here, we implemented the SEER-LAC system to demonstrate the direct detection of pathogen-specific DNA sequences present in E. coli O157:H7 on the lab-on-a chip. ZFPs custom-designed to detect shiga toxin in E. coli O157:H7 were immobilized on the cyclic olefin copolymer (COC) chip, which can function as a non-PCR based molecular diagnostic. Pathogen-specific double-stranded DNA was directly detected by engineered ZFPs immobilized on the COC chip with high specificity, providing a detection limit of 10 fmole of target DNA in colorimetric assay. Therefore, in this study, we demonstrated a great potential of ZFP arrays on the COC chip for further development of a simple and novel lab-on-a chip technology for detection of pathogens.